Longevity and Economic Growth in China and India Using a Newly Developed Bootstrap ARDL Model - Lin, Feng Li; Wang, Mei-Chih (Frontiers in Public Health, 2020)
In this study, a newly developed Bootstrap ARDL model is used to investigate the impact of longevity( the life expectation at birth) and alcohol consumption on economic growth (or GDP) in China and India over the period of 1992-2015. Empirical results indicate there is a long-run relationship among these three variables in China and India. Granger causality test based on Bootstrap ARDL model indicates that in China, an one way negative Granger causality running from economic growth to longevity and also negative from longevity to alcohol consumption. However, there is a positive bidirectional causality between longevity and alcohol consumption in India. The results have important policy implications for the government via focused health policy attention and anti-alcohol programs on population health.